Understanding the drivers of organic foods purchasing of millennials: Evidence from Brazil and Spain. - Molinillo-Jiménez, Sebastián; Vidal Branco, Murilo; Japutra, Arnold (Elsevier, 2019)
This paper examines the antecedents of millennials’ organic food purchasing. A conceptual framework, based on product characteristics, and consumers’ concerns and consciousness, is proposed. Data collection was conducted through a survey in two culturally and socioeconomically distinct countries (Brazil vs. Spain) to increase the robustness and generalizability of the results. The results show that product characteristics and consumer concerns improve millennials’ health and increase their social consciousness, which, in turn, increases their willingness to pay a price premium and their purchase frequency of organic foods. The findings show that the proposed model has high validity, with only one significant difference between the two countries. Theoretical contributions and managerial implications are discussed.
Pôlítica de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14106 (preprint)
Keywords: Alimentos - Consumo - Aspectos sociales; Food safety concern; Natural content; Environmental concern; Sensorial appeal; Health consciousness; Social consciousness; Willingness to pay a premium; Purchase frequency; Millennials; Organic food